2013
DOI: 10.1063/1.4773988
|View full text |Cite
|
Sign up to set email alerts
|

Properties of epitaxial BaTiO3 deposited on GaAs

Abstract: Articles you may be interested inStructural and dielectric properties of laser ablated BaTiO3 films deposited over electrophoretically dispersed CoFe2O4 grains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…However, the combined effect of the high temperature Ge oxide desorption at 800 C for 30 min and the 650 C growth temperature required for BTO during the MBE growth process led to crystallographic disorder at the BTO/(100)Ge interface. Contreras-Guerrero et al 22 demonstrated MBE grown epitaxial BTO on (100)GaAs with 8 Å STO buffer layer. In their study, it was hypothesized that the BTO layer is rotated by 45 with respect to GaAs layer suggesting that the BTO (110) planes are parallel to the GaAs (100) planes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the combined effect of the high temperature Ge oxide desorption at 800 C for 30 min and the 650 C growth temperature required for BTO during the MBE growth process led to crystallographic disorder at the BTO/(100)Ge interface. Contreras-Guerrero et al 22 demonstrated MBE grown epitaxial BTO on (100)GaAs with 8 Å STO buffer layer. In their study, it was hypothesized that the BTO layer is rotated by 45 with respect to GaAs layer suggesting that the BTO (110) planes are parallel to the GaAs (100) planes.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 BTO has also been used as a buffer layer for integration of Ge on Si and continues to be of interest for added functionalities on Si or Ge for low-power CMOS logic applications. However, integration of BTO on semiconductors faces numerous challenges such as: (i) the epitaxial nucleation requires oxide formation on the surface, 22 (ii) requirement of oxide buffer layer (e.g., BaSrO, BaO, MgO, SrTiO 3 (STO)) between the BTO and the parent substrate to ensure that BTO is c-axis oriented, [22][23][24][25][26][27] (iii) monolayer (ML) of strontium (Sr) metal as the nucleation layer, 28 and (iv) large lattice mismatch (>20%) with Ge-on-Si(001). 29 Vaithyanathan et al 30 suggest that a thick buffer layer of BaSrO is needed for c-axis oriented BTO when grown on Si.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inserting an ultrathin STO layer between BTO and Ge, one can impose compressive in-plane strain on BTO that can overcome tensile stress caused by the thermal expansion mismatch and thereby achieve BTO on Ge with out-of-plane polarization 5 ; a similar approach was recently used to grow BTO on GaAs. Ferroelectric switching of c-axisoriented BTO on STO-buffered GaAs was demonstrated by Huang et al 23 using preferentially oriented films with columnar crystallites, and by Contreras-Guerrero et al 24 using flat epitaxial films.…”
mentioning
confidence: 99%
“…This peak is deconvoluted into 41.7 eV (elemental arsenic) and 40.9 eV (AseGa). Therefore, at the interface (ZnO/SIeGaAs), in addition to the elemental arsenic, arsenic bonded with gallium (AseGa) is also present [33,34]. However, no signature related to As O (40.0 eV) or any other acceptor state was found in the XPS spectra [14].…”
Section: Resultsmentioning
confidence: 99%